Simulation of seasonal rainfall in the Philippines using a regional climate model - Dalida, Landrico U.Jr.; Argete, Josefina C. (Quezon City Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2010)
A Regional Climate Model Version 3 (RegCM3) was used to simulate the seasonal rainfall (June, July August and September 2001). The model performance was assessed on a smaller domain covering the Philippines using subjective analysis of rainfall pattern and computation of skill scores. The model was tested by shifting the domain 10 degrees to the left of the control run, ShL, and to the right, ShR. ShL covers mor landmass than bodies of water while ShR include more ocean than the control run. ShL and ShR were used to determine the effect of changing the boundary position. The model was then tested using different cumulus parameterization schemes : Grell with Fritsch Chappel closure (FC), Grell with Arakawa-Schubert closure (AS) and Kuo. Assessment of the model performance was first based on subjective analyses of the maps in order to determine how well the rainfall patterns were simulated.
Thesis (Ph.D.-Meteorology)--University of the Philippines Diliman
Keywords: Rainfall intensity duration frequencies -- Philippines